Aislamiento de microrganismos con la capacidad de biotransformar los ácidos biliares hyodesoxicólico y desoxicólico - Araujo Guayasamín, Misheel Enith (2014)
This research will seek to find microorganisms capable of biotransform steroid structures for acids and deoxycholic hyodeoxycholic are products Ursodeoxycholic acid synthesis. One major problem presented by the synthesis of ursodeoxycholic acid are industrially pollutants generated, so as to produce chemical synthesis processes which produce environmental pollution are realized. Chemical synthesis of ursodeoxycholic acid was developed in the 50s by Hofman and Fieser, who invented a method with a process that consists of 5 steps ( esterification , acetylation , oxidation, hydrolysis and reduction) for obtaining quenodexosicólico acid and from this with a process that consists of 4 steps (esterification , acetylation, oxidation and reduction) obtained ursodeoxycholic acid. Interest in the ursodeoxycholic acid occurs for use in the pharmaceutical field for the treatment of sandy gallstones. Through this research sought to reduce the steps of synthesis of ursodeoxycholic acid, reducing the environmental impact, finding microorganisms with a high capacity for biotransformation.